1999
DOI: 10.1056/nejm199901073400101
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Antimicrobial-Impregnated Central Venous Catheters

Abstract: The use of central venous catheters impregnated with minocycline and rifampin is associated with a lower rate of infection than the use of catheters impregnated with chlorhexidine and silver sulfadiazine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
2
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 741 publications
(172 citation statements)
references
References 16 publications
2
155
2
9
Order By: Relevance
“…Aseptic techniques for handling the catheters, 27 skin disinfection, 28 impregnating catheters with antibiotics or the use of anticoagulation [29][30][31][32][33] have been proven of value. A study of 356 non-tunneled catheters in cancer patients showed that impregnation of central venous catheters with minocycline and rifampicin was efficacious (3 vs 14 infections in impregnated vs nonimpregnated catheters) and safe in reducing catheter-related infections.…”
Section: Discussionmentioning
confidence: 99%
“…Aseptic techniques for handling the catheters, 27 skin disinfection, 28 impregnating catheters with antibiotics or the use of anticoagulation [29][30][31][32][33] have been proven of value. A study of 356 non-tunneled catheters in cancer patients showed that impregnation of central venous catheters with minocycline and rifampicin was efficacious (3 vs 14 infections in impregnated vs nonimpregnated catheters) and safe in reducing catheter-related infections.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter randomized trial, CVCs impregnated on both the external and internal surfaces with minocycline/rifampin were associated with lower rates of CRBSI when compared with the first-generation chlorhexidine-silver sulfadiazine impregnated catheters [91]. The beneficial effect began after day 6 of catheterization.…”
Section: Antimicrobial/antiseptic Impregnated Catheters and Cuffsmentioning
confidence: 99%
“…11,12 The antibacterial activity AgNPs The improvement of impregnation of medical devices with silver nanoparticles is that it protects both outer and inner surfaces of medical devices and there is the continuous release of silver ions providing good antimicrobial activity. 13 …”
Section: Introductionmentioning
confidence: 99%